Influence of Running and Walking on Hormonal Regulators of Appetite in Women - D. Enette Larson-Meyer; Sonnie Palm; Aasthaa Bansal; Kathleen J. Austin; Ann Marie Hart; Brenda M. Alexander (Hindawi Limited, 2012)
Nine female runners and ten walkers completed a 60 min moderate-intensity (70% VO2max) run or walk, or 60 min rest in counterbalanced order. Plasma concentrations of the orexogenic peptide ghrelin, anorexogenic peptides peptide YY (PYY), glucagon-like peptide-1 (GLP-1), and appetite ratings were measured at 30 min interval for 120 min, followed by a free-choice meal. Both orexogenic and anorexogenic peptides were elevated after running, but no changes were observed after walking. Relative energy intake (adjusted for cost of exercise/rest) was negative in the meal following running (−194±206 kcal) versus walking (41±196 kcal) (P=0.015), although both were suppressed (P<0.05) compared to rest (299±308 and 284±121 kcal, resp.). The average rate of change in PYY and GLP-1 over time predicted appetite in runners, but only the change in GLP-1 predicted hunger (P=0.05) in walkers. Results provide evidence that exercise-induced alterations in appetite are likely driven by complex changes in appetite-regulating hormones rather than change in a single gut peptide.